KEPERCAYAAN PENGGUNAAN SISTEM RESEP ONLINE PADA TENAGA KESEHATAN DI SURAKARTA - Dede Eka Putra; Didik Setyawan; Finisha Mahaestri Noor (Fakultas Ekonomi - Universitas Setia Budi, 2020)
This study aims to test the trust caused by technological knowledge, compatibility, and system security. Previous studies have not yet explained the role of trust in the relationship between technological knowledge, compatibility, and security in the intention to continue the online prescription system. Data was obtained through an online questionnaire that was distributed to health professionals using the Surakarta online prescription system. The sampling technique used was purposive sampling with a population of 200 health workers. Hypothesis testing is done by using SEM. The results of this study indicate that technology and security knowledge have a role in increasing trust to form intentions to use online prescription systems. There are hypotheses that are not supported by compatibility which is felt to have no role in increasing trust to form intentions using an online prescription system.